Predicting attendance of cancer patients: Care in general practice - Ngune, Irene; Jiwa, Moyez; McManus, Alexandra; Parsons, Richard; Hodder, R. (PNG Publications, 2014)
Objective: To examine the role of the theory of planned behavior (TPB) in influencing patients’ intention to attend follow-up visits with a general practitioner (GP). Methods: A questionnaire based on the TPB was used to assess colorectal cancer (CRC) patients’ intention to attend follow-up visits with a GP. Results: TPB factors accounted for 43.3% of the variance of intention for follow-up visits. Attitude alone explained 23.3% of the variance. Attitude and presence of other comorbidities significantly affected intention to visit a GP (attitude: R2=0.23, F [1, 65]=4.35, p < .01; comorbidity: R2=0.13, F [1, 65]=3.02, p < .05). Conclusion: Patients who believe their GP has the skills and knowledge to detect a recurrence and patients with other comorbidities have greater intention to visit their GP following treatment.